2016
DOI: 10.4103/1947-489x.210229
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the world health organization's healthcare system framework: A consensus development study in Libya

Abstract: Introduction: The World Health Organization (WHO) Health Systems Framework (HSF) with its 6 building blocks is a widely accepted tool for accurate evaluation of health systems. However, its role in the developing world has not been widely assessed yet. Methods: Six Questionnaires with 5-point Likert-scale were designed and distributed to all the attendees of Libya Health 500 (LH500) Conference, and collected just before the group discussion of Libyan health system's session. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…To the Editor, I read with interest the study by Aburawi and colleagues (1), but remain rather unclear as to what the aim of the survey was; explore the views of healthcare workers on the WHO Health System Framework (WHO-HSF) 6 pillars model (2,3)? or their own views about Libyan healthcare system and the problems it faces?…”
mentioning
confidence: 99%
“…To the Editor, I read with interest the study by Aburawi and colleagues (1), but remain rather unclear as to what the aim of the survey was; explore the views of healthcare workers on the WHO Health System Framework (WHO-HSF) 6 pillars model (2,3)? or their own views about Libyan healthcare system and the problems it faces?…”
mentioning
confidence: 99%
“…However, its role in the developing world has not been widely assessed yet (1). In the current issue of this Journal, a consensus development study on the applicability of the WHO healthcare system frameworks to Libya is reported (2). The study was a collaboration between the WHO-East Mediterranean Regional Office (WHO-EMRO) and the Libyan ministry of health.…”
mentioning
confidence: 99%
“…The aim of the survey was to explore the views of healthcare workers in Libya on the WHO Health System Framework (WHO-HSF) 6 pillars model (2)(3)(4). The attendants were encouraged to express their views about the Libyan healthcare system and the problems it faces.…”
mentioning
confidence: 99%